Menyelidiki Loyalitas Millenial pada Transportasi Online; Studi Mediasi berbasis SEM-PLS - Ashoer, Muhammad; Syahnur, Muhammad Haerdiansyah; Taufan, Rezky Ratnasari; Siangka, Andi Nursiskawanti (Benefit: Jurnal Manajemen dan Bisnis, 2020)
The massive transformation of consumer behaviour on the online transportation network platform in Indonesia has still not yet answered comprehensively. We have identified and evaluated several latent constructs based on prior research review. Hence, we investigate the effect of electronic customer relationship management (e-CRM) on e-satisfaction and e-loyalty of online transportation costumer. We applied a causality approach method to measure the primary data, and then we selected respondents with purposive sampling technique which have met the predetermined criterion. In total, there was 142 customer have participated in this online survey. To examine the primary data, we used the variance-based analysis ofÂ Structural Equation ModelÂ (SEM) - Partial Least Square (PLS) analytical instruments. The results have a significant managerial and theoretical contribution to the stakeholder to make a customer keep loyal in ever-changing e-commerce business in Indonesia.